Digitale Arbeitswelten und Arbeitsbeziehungen: What you see is what you get?; Digital working and industrial relations: What you see is what you get? - Sabine Pfeiffer (Industrielle Beziehungen, 2019)
Der Beitrag versteht sich als (selbst-)kritische Reflexion ub̈er die Arbeitsforschung und ihren Beitrag zum Verstan̈dnis der aktuellen Digitalisierung. Diskutiert wird, welche Einschran̈kungen sich derzeit ergeben, weil 1. ub̈erwiegend mit Fallstudien in vergleichsweise interessenpolitisch gut gestellten Kontexten und zu punktuellem Digitalisierungseinsatz geforscht wird; 2. die konkreten Besonderheiten der aktuellen Digitalisierungstechnologien in der Forschung wie in der betrieblichen Interessenspolitik weitgehend ausgeblendet werden und 3. der gesellschaftliche und alles andere als interessenpolitisch neutrale Digitalisierungsdiskurs in seiner Wirkmac̈htigkeit fur̈ betriebliche Entscheidungsund Aushandlungsprozesse unterschaẗzt wird. Die Akteure der Arbeitsbeziehungen, ebenso wie die ub̈er und fur̈ sie Forschenden, sind herausgefordert, die sich teils erst in der Zukunft realisierenden Folgen aktueller Anschaffungs- und Gestaltungsentscheidungen heute zu verstehen und zu bearbeiten, sie mus̈sen daher mit einer mehrdimensionalen Transformationsdynamik umgehen. Der Beitrag begrun̈det aus dieser Perspektive (und plad̈iert fur̈) eine methodische und thematische Erweiterung der Arbeitsforschung. – – The contribution is conceptualized as a (self-)critical reflection on labour research and its contribution to the understanding of the prevailing digitalisation. It will be discussed which limitations arise within the current research approach because 1. case studies are predominantly conducted within contexts of comparatively well-working interest policy, strong work councils, and on the selective use of digitalisation; 2. the specific characteristics of current digital technologies are largely ignored in both research and corporate interest policy; and 3. the impact of the societal and anything but neutral discourse on digitalisation for corporate decision-making and labour-related negotiation processes is underestimated. The actors in industrial relations, as well as those who conduct research on and for them, are challenged to understand and deal with the consequences of current decisions about the investments, and the application and design of digital technologies - consequences for work and labour relations which will partly only emerge in the future, but must be shaped and negotiated today. Management and work councils must therefore deal with a multidimensional dynamic of transformation, and labour research should provide more helpful insights to support the actors of labour relations in this process. From this perspective, the contribution justifies (and pleads for) a methodological and thematic extension of labour research.
Keywords: J53; J83; M12; 330; Industrie 4.0; digitale Transformation; digitaler Kapitalismus; Mitbestimmung; industrielle Beziehungen; Industrie 4.0; digital transformation; digital capitalism; co-determination; labour relation